PENGARUH MEDIA ARANG KAYU JATI PADA PROSES PACK CARBURIZING TERHADAP KOMPOSISI KIMIA DAN KEKERASAN BAJA KARBON RENDAH - Shultoni Mahardika; Mohammad Thoriqul Hidayat (Otopro, 2021)
Low carbon steel is steel with a carbon element content of less than 0.25%. This type of steel is widely used in spare parts motorbikeproducts after market. This type of product has a lower hardness level when compared toproducts Genuine Parts. Due to the low hardness value of the steel material when compared to Genuine Parts products, this product wears out faster. Due to this, engineering was carried out to increase the hardness of steel. One way is by using themethod pack carburizing. Theprocess pack carburizing in this study uses teak wood charcoal as a carburizer. This process is done by pre-heating the material in thebox carburizing pack at a temperature of 650 C. After pre-heating, the temperature was increased to 900áµ’C and different holding times were carried out, namely 5.6 and 7 hours. After that, the cooling process is carried out with water. The results obtained were that thematerial pack carburized had a higher carbon value as the holding time increased. The carbon value before treatment was 0.12%, then there was an increase to 1.03% at the holding time of 5 hours, 1.18% at the holding time of 6 hours and 1.37% at the holding time of 7 hours. The results of the hardness testing before treatment were 46.4 HRA on average increased to 83.66 HRA, 84.69 HRA and 84, 82 HRA at 5 hours, 6 hours and 7 hours detention. However, when doing statistical tests, it is not recommended to hold the heating time up to 7 hours when using this medium. This is because the comparison of changes in violence between 6 hours and 7 hours of detention did not show a significant increase in violence